Pengaruh Komunitas dan Ekuitas Merek Terhadap Minat Pembelian Ulang Motor Sport Kawasaki di Sidoarjo (Studi Pada Komunitas SINEVO) - Shofi Asyaduddin Sakti; Febrina Hambalah; Herman (Journal Of Accounting and Business, 2022)
This study aims to examine the influence of brand community and equity on the intention to repurchase Kawasaki motorcycle sport products in Sidoarjo in the study of the SINEVO (Sidoarjo Ninja Evolution) community. The data analysis technique used multiple linear regression technique, saturated sampling technique. Data collection techniques used observation or observation techniques, and questionnaires (questionnaires). Furthermore, the research data was processed using SPSS version 23. The results of multiple linear regression analysis showed that the coefficient of determination was 0.789 so that it was stated that brand community and brand equity were able to influence repurchase interest by 79%. The regression coefficient values are all positive, namely 3.180 for the constant, 0.221 for the brand community, and 0.282 for the brand equity. While the results of the F test showed a significance value of 0.000 <0.05, indicating that this regression model was feasible to use. The results of the hypothesis test explain that the t-test of the brand community variable obtained a significance value of 0.010, and the brand equity variable of 0.000 so that it can be concluded that brand community and brand equity have a positive and significant effect on repurchasing interest in Kawasaki sport motorbikes in Sidoarjo, a case study on the SINEVO community (Sidoarjo Ninja Evolution).